Relationship between body size variables and performance in repeated sprints test in young soccer players - Borges, P. H.; Costa, J. C.; Silva, L. F. R.; Gouvêa, M. A.; Ronque, E. R. V. (Isokinetics and Exercise Science, 2018)
BACKGROUND: During the first two decades of life, athletes pass through intense changes in body size, which can directly influence physical fitness, especially anaerobic tasks. OBJECTIVE: We examined which body size variables can discriminate the level of anaerobic performance in young soccer players. METHODS: The sample was composed of 102 regional players (14.5 ± 1.6 years) belonging to youth soccer clubs at a regional level. Anthropometric measures of weight and height were carried out. A left hand-wrist radiograph was taken to identify bone age of the players. To assess anaerobic fitness, the 7-sprints test protocol was applied. To analyze the relationship between body size variables and anaerobic capacity, the Pearson correlation coefficient was used. Through the non-hierarchical k-means cluster method, players were grouped into three anaerobic levels: high (n = 22), average (n = 44), and low (n = 36). Subsequently, discriminant analysis (stepwise method) was used to verify which growth variable discriminates the level of anaerobic fitness (p < 0.05). RESULTS: Results indicated that 7 sprints performance is related to chronological age (r = - 0.41; p < 0.01), bone age (r = - 0.43; p < 0.01), height (r = - 0.33; p < 0.01), and body mass (r = - 0.23; p < 0.01) in U-14 soccer players. Height was able to discriminate the level of anaerobic fitness across U-14 players ( = 0.46, = 0.68, X 2 (6) = 19.89). No significant predictors were identified for U-17 anaerobic performance. DISCUSSION: Body size is related to 7 sprints performance in U-14 youth players, while biological maturation seems to influence physical fitness.